Practical-empirical theology as a possible methodological approach for a further development of the Latin American theology of the signs of the times. (Teología, 2022)
The theology of the signs of the times is already part of the Latin American theological tradition. All in all, this theology raises two questions that remain open: what could be meant by locus theologicus, applied in this case to current history, and, therefore, the role that it would have for theology; and, on the other hand, how can theology study this theological place in a methodically founded way. Seeking to contribute particularly to the second issue, the following article will collect the most recent studies regarding the first aspect as fundamental bases, to then focus on the second question, trying to show how practical theology and the method of empirical theology can be a contribution to address this methodological challenge. The article will conclude by commenting on the potential that the conjunction of both elements –the understanding of current history as a theological place and empirical practical theology– can have for a further development of the theology of the signs of the times in the continent.
Keywords: Signs of the times; Theological place; Latin American theology; Practical theology; Empirical theology; Theology of history